Modulation of mitochondrial function as a therapeutic strategy for Stargardt disease and an exploration of the genetic architecture of Stargardt disease in Ireland - Post, Iris Johanna (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2024)
Inherited retinal degenerations (IRDs) are an extremely heterogeneous group of disorders, together representing the most common cause for vision loss in young people. An estimated 5.5 million people globally are living with an IRD. The most common IRD caused by a single gene is Stargardt disease type 1 (STGD1), which is caused by biallelic mutations in ABCA4 and vision loss can occur as early as the first decade of life. No therapies are available to cure or alleviate symptoms for this IRD. One of the main limiting factors in designing gene therapies is transport of the transgene into in vivo cells. AAV vectors, which are able to transduce post-mitotic cells such as retinal cells well and are low immunogenic, can only carry a gene with a maximum size of 4.5kb. The cDNA of ABCA4 encompasses 6.8kb, so a different approach is essential for designing a therapy for STGD1. This PhD thesis investigates the possibility to modulate mitochondrial function as a therapeutic strategy for Stargardt disease. ABCA4 dysfunction leads to the accumulation of toxic vitamin a aggregates (A2E) in photoreceptor cells and retinal pigment epithelium. A2E is a major component of the autofluorescent pigment complex lipofuscin, which causes downregulation of mitochondrial function, increased levels of oxidative stress, and ultimately, cell death. Utilising a codon-optimised, humanised yeast homolog for NADH Dehydrogenase, NDI1, we investigated if the effect of ABCA4 dysfunction on mitochondrial welfare could be ameliorated. Chapter 3 of this thesis describes the exploration of AAV.CAG.ophNDI1 as a therapeutic strategy in a variety of cell models of disease. Models were based on RPE-like cell line ARPE19 cells and primary porcine RPE cells that were insulted with either NaIO3 or A2E. Treatment with AAV.CAG.ophNDI1 improved mitochondrial function and reduced levels of Reactive Oxygen Species (ROS) in all models. We then extended the investigation to mouse models of disease, which are presented in chapter 4. The model, Abca4-/- mice, was first characterised extensively. Then, they received subretinal injections with various doses of AAV.CAG.ophNDI1 in one eye, while the second eye was only injected with PBS to serve as a control. Here, we found that cellular ROS levels could be significantly reduced with the therapy. Furthermore, we showed, for the first time, that lipofuscin levels can be reduced through the modulation of mitochondrial function. Additionally, we recognise that it is extremely important to genetically diagnose everyone living with IRDs or other forms of sight loss in order to know if any such individual is eligible for approved gene therapies or clinical trials. The Target 5000 project aims to provide clinical care and genetic diagnoses for all Irish IRD patients. A total of 212 people have been successfully diagnosed with biallelic, ABCA4-related Stargardt disease through Target 5000. Utilising Target 5000 data, chapter 5 of this thesis provides and extensive overview of the genetic architecture of Stargardt disease on the island of Ireland. A case study is presented on a variant that appears to be enriched in the Irish population, p.Cys54Tyr. Furthermore, a short overview is given on the prevalence of PROM1, PRPH2, and ELOVL4 in the Target 5000 cohort, as dysfunction in these genes can give rise to Stargardt-like phenotypes. This PhD thesis outlines a gene therapy strategy that is independent of the gene involved in disease. Employing a transkingdom complex I gene therapy (NDI1) to modulate mitochondrial function can provide therapeutic benefit in in vitro and in vivo models of disease. Strategies targeting common pathways of disease may provide a therapeutic option for degenerative conditions whose genetic diagnosis remains elusive.
APPROVED